ANATOMIC CHARACTERISTICS OF THE STEM OF MANGO (Mangifera spp.) IN BANDAR LAMPUNG - M. Ramdan Syahputra; Yulianty Yulianty; Martha Lulus Lande; Suratman Suratman (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2021)
Mango is one of the most widely grown plants in Indonesia. The characteristic that distinguishes one type of mango from another is to observe its anatomy. Anatomical research on the mango branch has not been done much, especially in Bandar Lampung. The purpose of this study was to determine the diameter and pith radius of the mango (Mangifera spp.) branch in Bandar Lampung City. This research was carried out from January to April 2021 at the Botanical Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, University of Lampung. This study uses a survey method with Simple Random Sampling in 20 sub-districts in Bandar Lampung City. Parameters measured included tracheal diameter, tracheal density, arrangement and type of pith radius, pith radius height, and pith radius width. Data analysis used descriptive analysis by explaining the data obtained in the form of tables and photos. The results showed that there were differences in the average size of the tracheal diameter, tracheal density, height, and width of pith radius of the five mango branch samples. The average diameter of the largest trachea is found in Golek and the smallest tracheal diameter is found in Kweni. The highest average tracheal density is found in Arumanis and the smallest tracheal density is found in Golek. The arrangement and type of pith radius of the fifth mango are uniseriate and heterocellular. The average height of the largest pith radius is owned by Indramayu and the smallest is owned by Golek. While the average width of the largest pith radius is owned by Golek and the smallest is owned by Gedong.